Postcard : Notice of meeting - Arne, Betty L.
1938-01-08 038-0171-001 POST CARD THE ADDRESS TO BE WRITTEN ON THIS SIDE H.V. Tewson, Esq. , Trades Union Congress, Transport House, Smith Square, S.W.1. 292/946/38/171(I)